The Influnce of Discipline, Work Stress, and Organizational Culture on Work Productivity of PT Telkom Indonesia Bogor - Ratasya Suci Asmala; Zackharia Rialmi; Subur subur (Universitas Darussalam Gontor, 2021)
The purpose of this research is to be able to know the influence of work discipline, work stress and organizational culture on the work productivity of PT Telkom Indonesia Witel Bogor. The population is all employees of PT Telkom Indonesia Witel Bogor with a total of 174 employees. The number of samples used in this study was 64 employees with slovin use. Data processing the dissemination of questionnaires and using quantiative data analysis techniques using the statistical methode partial Least Square (PLS). The test result of this study are, (1) work discipline has significant and positive effect on work productivity, (2) work stress has a significant and negative effect on work productivity, (3) and organizational culture has a significant and positive effect on work productivity of PT Telkom Indonesia Witel Bogor. Keywords: organizationa culture, work discipline, work productivity, and work stress.